2011
DOI: 10.1093/petrology/egr063
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Peritectic Garnet in the Peraluminous Cardigan Pluton, New Hampshire

Abstract: The peraluminous Cardigan Pluton of New Hampshire contains restitic garnetites with abundant peritectic garnet that serves as a basis for comparison with garnet in the host-rock. The peritectic garnet is inclusion-rich and contains high concentrations of heavy rare earth elements (HREE), Sc, and Zr and low concentrations of Zn, P, and U. The high HREE, Zr, and Sc result from biotite and zircon melting, buffering liquid compositions. Because the HREE and Sc are compatible in garnet, the peritectic garnet is ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Support is also provided by rare enclaves of strongly melt-depleted residue in granite, such as that described by Solar and Brown (2001a), and rare meter-sized pods consisting of 50-70 vol% garnet (with sillimanite, biotite, plagioclase, and quartz), such as those described by Dorais et al (2009). In the latter example, from the Cardigan pluton in New Hampshire, whole-rock chemistry suggests that the garnetites either are restites or represent melt-depleted xenoliths; similar neodymium and strontium isotope composition of garnetite and granite, and detailed mineral chemistry reported by Dorais and Tubrett (2012) support an interpretation as restite. Dorais et al (2009) calculated a magma-ascent rate of >1000 km/yr and proposed that fast ascent inhibited restite dissolution in the Cardigan pluton; they suggested that slower rates of ascent might account for the paucity of restite preserved in most peraluminous granites.…”
Section: Fluid-absent Hydrate-breakdown Meltingmentioning
confidence: 66%
“…Support is also provided by rare enclaves of strongly melt-depleted residue in granite, such as that described by Solar and Brown (2001a), and rare meter-sized pods consisting of 50-70 vol% garnet (with sillimanite, biotite, plagioclase, and quartz), such as those described by Dorais et al (2009). In the latter example, from the Cardigan pluton in New Hampshire, whole-rock chemistry suggests that the garnetites either are restites or represent melt-depleted xenoliths; similar neodymium and strontium isotope composition of garnetite and granite, and detailed mineral chemistry reported by Dorais and Tubrett (2012) support an interpretation as restite. Dorais et al (2009) calculated a magma-ascent rate of >1000 km/yr and proposed that fast ascent inhibited restite dissolution in the Cardigan pluton; they suggested that slower rates of ascent might account for the paucity of restite preserved in most peraluminous granites.…”
Section: Fluid-absent Hydrate-breakdown Meltingmentioning
confidence: 66%
“…Data reduction was done using the Iolite software package (Paton et al, 2011). For more analytical details, see Dorais and Tubrett (2012).…”
Section: B L U E C a M B O D I A N Z I R C O Nmentioning
confidence: 99%
“…In specimen C93, garnet is fairly homogeneous in major elements (Figure 4d), yet exhibits strong compositional variation in trace elements (Figure 6m-p), which follows the textural zonation (Figure 3c). The high HREE values and low (Gd/Yb) N ratios and the prominent negative Eu anomaly in the peritectic garnet core indicate that the garnet core grew from a melt enriched in HREE and depleted in Eu, probably due to the progressive breakdown of zircon, mica and/or monazite (Dorais & Tubrett, 2012;Yakymchuk & Brown, 2014) in the feldspar (plagioclase±orthoclase) stability field (as predicted by the pseudosection; Figure 12a). The slight rimward depletion in HREE away from the core could indicate fractionation of these elements in the melt.…”
Section: Ree In Garnet: Insights Into Garnet Growth Resorption Andmentioning
confidence: 96%